Bertahan Hidup Dalam Kubangan Lumpur (Studi tentang Korban Lumpur Lapindo di Desa Glagaharum Kecamatan Porong Sidoarjo) - Suryaningsih, Adelia; Handayani, Baiq Lily (e-Sospol, 2017)
Abstract The incident of Lapindo hot mudflow happened on May 29, 2006. The Glagaharum village was one of the villages affected by the incident, which was as many as ± 400 households. Most of the victims of the Lapindo mudflow chose to move to other areas, and some others chose to stay in the area of Lapindo mud. The theory used was a framework of thinking of Pierre Bourdieu about habitus. This research used descriptive qualitative method. The research results showed that victims of Lapindo mudflow decided to survive in the Glagaharum village because they already had capital as a source of strength in facing the battle arena which was occurred in the area of Lapindo mud especially Glagaharum village. Capital used as a source of strength by the victims of Lapindo mudflow, such as: (1) the orientationof social capital. It was in the form of no information to move, no have another choice, fear of new environments, and relation to the neighbors; (2) the orientation of economic capital. It was in form of not capable of managing compensation, occupational factors, economic barriers, waiting for the construction of the house, and waiting for the children graduate; (3) the orientation of cultural capital.It was in the form of relation to the residence and the traditional mindset.